Analisis Kemampuan Berpikir Kritis Mahasiswa Dalam Menyelesaikan Permasalahan Bilangan Bulat Berbasis Media Realistik - Indri Anugraheni (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
The purpose of this study is to describe the ability of college students to think critically in solving integer problems using realistic media. This research is a qualitative descriptive study. The research subjects were 47 elementary school student teachers of FKIP Satya Wacana Christian University, who took realistic mathematics courses. The data collection techniques in this study were tests of college students' critical thinking skills in groups. Critical thinking test results are analyzed by describing college students' thinking abilities. The results of the study note that: the students are able to analyze, evaluate and create operations of addition and subtraction of integers by 24.26%; the students are able to analyze, evaluate but still unable to create problem solving with realistic mathematics media by 34.56%; the students are able to analyze but have not been able to evaluate and accelerate problem solving to a maximum of 13.97%; the students have not been in maximum ability in analyzing mathematical problems and have not been able to evaluate and create problem solving by 27.21%.